Quasispecies diversity determines pathogenesis through cooperative interactions in a viral population - Vignuzzi, Marco; Stone, Jeffrey K.; Arnold, Jamie J.; Cameron, Craig E.; Andino, Raul (Nature, 2006)
Viruses, where wrong is right The replication of RNA viruses is associated with a higher mutation rate than is seen in organisms using DNA as their genetic material. This can produce nonviable individuals but also, it has been suggested, some useful variation that could enhance the fitness of virus populations by allowing them to adapt to changing environments encountered during infection. Until now there has been no experimental support for this suggestion, known as the ‘quasispecies’ hypothesis. But now a search for viruses that copy their genome too accurately has provided support for this idea. Poliovirus isolates carrying a ‘super accurate’ RNA polymerase are less varied and less infectious than normal viruses. These results could have implications for the development of antiviral drugs. An RNA virus population does not consist of a single genotype; rather, it is an ensemble of related sequences, termed quasispecies 1 , 2 , 3 , 4 . Quasispecies arise from rapid genomic evolution powered by the high mutation rate of RNA viral replication 5 , 6 , 7 , 8 . Although a high mutation rate is dangerous for a virus because it results in nonviable individuals, it has been hypothesized that high mutation rates create a ‘cloud’ of potentially beneficial mutations at the population level, which afford the viral quasispecies a greater probability to evolve and adapt to new environments and challenges during infection 4 , 9 , 10 , 11 . Mathematical models predict that viral quasispecies are not simply a collection of diverse mutants but a group of interactive variants, which together contribute to the characteristics of the population 4 , 12 . According to this view, viral populations, rather than individual variants, are the target of evolutionary selection 4 , 12 . Here we test this hypothesis by examining the consequences of limiting genomic diversity on viral populations. We find that poliovirus carrying a high-fidelity polymerase replicates at wild-type levels but generates less genomic diversity and is unable to adapt to adverse growth conditions. In infected animals, the reduced viral diversity leads to loss of neurotropism and an attenuated pathogenic phenotype. Notably, using chemical mutagenesis to expand quasispecies diversity of the high-fidelity virus before infection restores neurotropism and pathogenesis. Analysis of viruses isolated from brain provides direct evidence for complementation between members in the quasispecies, indicating that selection indeed occurs at the population level rather than on individual variants. Our study provides direct evidence for a fundamental prediction of the quasispecies theory and establishes a link between mutation rate, population dynamics and pathogenesis.